(untitled) - E A Newsholme (Chichester, 1983)
This book is designed to provide students of the medical and biochemical sciences with a complete grounding in basic metabolic biochemistry. In addition the subject is extended by an explanation of how each metabolic pathway is directly refated to physiology, pharmacology and clinical medicine. The book will be of interest to first and second year biochemistry and physiology students and to medical students during their preclinical and clinical studies. The text has an extensive bibliography to enable students to follow up points of interest and clinical cases.
Keywords: metabolism